Measurement theory in action case studies and exercises - Shultz, Kenneth S.; Whitney, David J.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2005)
Clarifying major topics in classical & modern test theory, this book employs case studies depicting typical dilemmas, & offers exercises including brief in-class assignments, lab tasks that require the use of statistical analysis software & course-long test development projects.
Includes bibliographical references and indexes.
Specialized.
Description based on print version record.
Keywords: Psychometrics -- Case studies; Psychometrics -- Problems, exercises, etc; Electronic books